Die Kritik der marxistischen Rechtstheorie: Zu Paschukanis' Begriff der Rechtsform - Obermayr, Linda (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Eugen Pashukanis' concept of the legal form culminates in the dialectics of freedom and domination of bourgeois society. In this context, law is not understood as an instrument, but is deliberated upon as a form, independent of its concrete content. Against the utopian attempt to imagine a beyond of law, Pashukanis' theory of law is, at last, asserted not as a theory of how law should be, but as a theory of how law should be conceptualized and, that is, criticized.